Rise in erythropoietin concentrations in experimental Trypanosoma congolense infection of calves - Buza, J.J.; Logan-Henfrey, L.L.; Andrianarivo, A.G.; Williams, D.J.L. (Elsevier, 1995)
A bioassay was used to measure erythropoietin (EPO) concentrations in calves with haemorrhagic anaemia due to blood loss and in calves with anaemia due to Trypanosoma congolense infection. The bioactivity of EPO was measured in the assay by its stimulatory effect on 125I-deoxyuridine incorporation in spleen cells from phenylhydrazine-treated mice. Erythropoietin concentrations in blood-volume-depleted calves were elevated 6 h after blood loss, maximal (1225 mU/ml) at 33 h and below detection limits at 72 h. Reticulocytes (0.05 ± 0.1%) appeared in blood by 72 h, peaked at 120 h and disappeared from the circulation by 7 days after bleeding. The packed cell volume (PCV) started increasing at 120 h and reached near pre-bleeding values by 14 days. In T. congolense-infected calves, parasites were first detected in the peripheral blood 12 days post-infection (dpi). Parasitaemia peaked (5 x 105 trypanosomes/ml of blood) at 15-18 dpi and, thereafter, several waves of parasitaemia were observed, but the peaks gradually diminished. Undiluted plasma from T. congolense-infected calves suppressed 125I-deoxyuridine incorporation into spleen cells from 13 dpi onwards. The suppressive effect of plasma was partly negated by five-fold dilution, which made possible the detection of increased EPO concentrations during the acute and chronic stages of the anaemia. The highest EPO peaks, reaching 2300 mU/ml in one calf, were detected during the chronic stage of the infection. At 15-39 dpi, there was a transient bone-marrow erythropoietic response characterized by an increase in mean corpuscular volume and a decrease in mean corpuscular haemoglobin concentration but with few reticulocytes (0.4%). However, from 76 dpi onwards, this response waned despite low PCV and elevated EPO concentrations. These results suggest that there is an ineffective erythroid response in the face of elevated EPO concentrations during bovine trypanosomiasis. The negative effect of plasma and serum from trypanosome-infected calves on the in-vitro bioactivity of EPO suggests the presence of inhibitory factors.